Comparison of Local Infection, Dwell Time and Pain in Peripheral Venous Cannulation passed by Experts versus General Inserters at a Tertiary Care Hospital - Elleyyeen Avais; Syed Anees Ahmed Gardezi; Muhammad Uzair; Iqbal, Muhammad; Hassan Javed (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the incidence of local infection, Dwell time and pain associated with peripheral venous cannulation (PVC) when performed by experts versus general inserters in a tertiary care hospital. Study Design: Randomized controlled trial (IRCT20230925059510N1). Place and Duration of Study: Inpatient Departments, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Apr to Sep 2023. Methodology: Patients were randomized into Group-A (insertion by experts) and Group-B (insertion by general staff) with 175 participants each. Primary variables measured were total dwell time, incidence of local site infection, failure of insertion by the inserter, pain as assessed on the Visual Analog Scale (VAS), and patient satisfaction assessed by a 7-point standard Likert Scale (0=Extremely dissatisfied to 7=Extremely satisfied). Results: Failure of insertion was seen in 05(2.9%) patients in Group-A versus 40(22.9%) patients in Group-B (p=0.045). Assessment of median pain scores on insertion on the Visual Analog Scale showed median scores of 3.00 (IQR=0.00) in Group-A versus 4.00 (IQR=1.00) in Group-B (p<0.001). Patient satisfaction post-procedure as assessed on standard 7-point Likert Scale showed median satisfaction scores of 6.00 (IQR=1.00) in Group-A versus 4.00 (IQR=1.00) in Group-B. Conclusion: We concluded that even though expert inserters result in decreased failure rates and better patient pain scores and compliance, their availability as a separate team in resource constrained setups cannot be recommended at present.